A Pneumatological Renaissance: The Pentecostal Imagination of Jennings’ Acts Commentary - Rodriguez-Gungor, Edwin (2025)
This article explores Willie James Jennings’ Acts as a transformative work that bridges theological depth with practical engagement, presenting the book of Acts as a vivid depiction of life shaped by the Spirit of God. Drawing from Jennings’ poetic and imaginative exegesis, the analysis highlights his ability to make ancient texts accessible and relevant, particularly to those invested in the pneumatological dimensions of Christian faith. The discussion situates Jennings within the broader context of a ‘pneumatological renaissance’, as described by Veli-Matti Kärkkäinen, and echoes the growing hunger for the Spirit’s work noted by theologians like Elizabeth Dreyer. The article concludes with a call for theologically rich yet practical works like Jennings’ to inspire contemporary preaching and renewal in church life, affirming their potential to foster spiritual growth and communal transformation.
Keywords: Preaching; pneumatological renaissance; Pneumatology; Holy Spirit; Acts; Willie James Jennings